Relationship Between Emotional Intelligence and Self-Esteem among Nursing Students - Fekry Bsharat MSN (SAGE Publishing, 2024)
Introduction Nursing students must be able to detect the standpoints and demands of various sorts of individuals, as well as be competent in taking into account individual emotional reactions, self-confidence, stress management, and social role promotion. Objective The purpose of this study was to assess the relationship between emotional intelligence and self-esteem among fourth-year nursing students. Methods The study was a cross-sectional study. Data were collected from 225 nursing students through a convenience sampling method in spring 2023 at Arab American University. The instruments of the study included "Schutte Self Report Emotional Intelligence Test" and the "Rosenberg self-esteem scale." Results The analysis indicated that the emotional intelligence mean was 151.3 ± 1.9 (ranging from 33 to 165), which is high. Also, the analysis indicated that the self-esteem of the nursing students was high 24.3 ± 3.5 (ranging from 0 to 30). Furthermore, the analysis showed that there was a moderately positive relationship between nurses' emotional intelligence and self-esteem. Conclusion The emotional intelligence and self-esteem among fourth-year nursing students were high. Also, self-esteem was found to have a moderately positive relationship with emotional intelligence and utilizing emotions.